Soluble vascular cell adhesion molecule-1 levels and severity of dengue hemorrhagic fever in children - Nolitriani Nolitriani; Rinang Mariko; Mayetti Mayetti (Paediatrica Indonesiana, 2021)
Background The clinical manifestations of dengue infection vary widely, ranging from asymptomatic to severe forms that can cause death. In severe infections, the expression of soluble vascular cell adhesion molecule-1 (sVCAM-1) in endothelial cells is reportedly excessive, causing endothelial cell gaps through VE-cadherin and plasma leakage, which is the basic mechanism for shock in dengue hemorrhagic fever (DHF).